Pathogen Infection as a Possible Cause for Autoimmune Hepatitis. (4th July 2014) - Christen, Urs; Hintermann, Edith
<x xml:space="preserve">Abstract</x> Autoimmune disorders afflicting the liver comprise the bona fide autoimmune diseases, primary biliary cirrhosis, primary sclerosing cholangitis, and autoimmune hepatitis as well as drug-induced autoimmune-like diseases, such as halothane hepatitis. Whereas drug-induced forms of acute or chronic hepatitis often have a clear triggering factor, the etiology of classical autoimmune liver diseases is only poorly understood. Besides a genetic component present in disease susceptible individuals, environmental triggering factors are likely to play a role in the initiation and/or propagation of the disease. In this article, we will review on current evidence obtained from epidemiological associations, case studies, and findings in animal models for pathogens, to be involved in the etiology of autoimmune liver disease with a special focus on autoimmune hepatitis.